Grape expectations: how the proportion of white grape in Champagne affects the ratings of experts and social drinkers in a blind tasting - Harrar, V; Smith, B; Deroy, O; Spence, C (BioMed Central, 2013)
Background: Champagnes (or sparkling wines that are made using the ‘méthode champenoise’) are composed of white and/or red wine grapes. Their relative proportions are thought to contribute to a sparkling wine’s distinctive flavour profile, but this has not yet been tested empirically. We, therefore, conducted a blind tasting experiment in which the participants had to report the perceived proportion of white grapes in a range of seven sparkling wines (including six Champagnes). Results: The participants, including four expert, six intermediate, and five novice Champagne tasters, were unable to accurately judge the percentage of white grapes in the wines. Instead, the perceived proportion of white grape was correlated with the dosage and alcohol content of the wines. The hedonic ratings for the Champagnes did not correlate with price. Further, the more expensive Champagnes were only appreciated by the expert tasters. Conclusions: Dosage and alcohol content appear to be the two attributes that tasters rely on when judging the contribution that different grape types make to the distinctive flavour of a sparkling wine. In the case of Champagne, flavour perception relies on a complex combination of factors including alcohol content, dosage, price expectancy, and experience with the product. The present results have implications for marketing Champagnes; they might be better if focused on the distinctive characteristics of each cuvee, or simplicity (blends versus non